Bioecological Aspect of Lakepe (Betta raja) in Natural Habitat of Bandar Tinggi Village, Rantau Selatan District, Labuhan Batu Regency - Khairul; Machrizal, Rusdi; Wahyungsih, Hesti (TALENTA Publisher, Universitas Sumatera Utara, 2020)
Lakepe (Betta raja) is a wild fish species inhabiting water region in Labuhanbatu regency. The fishes are commonly known to inhabit steady and unpolluted streams. The aquatic environmental condition and its ecology will determine the survivability and breeding of Betta raja in its natural habitat.A study of its ecological aspect is needed to obtain any physicochemical characteristics of natural habitat which may act as limiting factor to Betta raja presence. In this study, physicochemical characteristics of water are measured, i.e temperature (T), velocity, pH, dissolved oxygen (DO), biological oxygen demand (BOD), chemical oxygen demand (COD), total dissolved solid (TDS), and total suspended solid (TSS). The environmental condition are measured in the field (in situ) while other parameters, i.e DO, BOD, TDS, and TSS are analyzed in the laboratory. The results showed that the physicochemical characteristics of B. raja habitat are: T (26oC), velocity (0.05 m/s), DO (6.9 mg/L), BOD (3.27 mg/L), COD (8.26 mg/L), TDS (22.1 mg/L), and TSS (5.1 mg/L). The sizes of wild caught B. raja are ranged between 6.3–94.0 cm with body masses of 1.1–4.8 g.